Maintaining Character Education During and After Pandemic - Aziz, Abdul; Suprayitno, Iswahyudi Joko; Prahmana, Rully Charitas Indra; Prasetyo, Puguh Wahyu (Proceeding International Conference on Mathematics and Learning Research, 2021)
The focus of education during the COVID-19 pandemic is more likely to be cognitive and learning. There has been no maximum effort in strengthening character education. The limited face-to-face meetings in learning have an impact on character education. This situation also applies at the university level. Prospective mathematics teachers who are currently studying have an essential role in building good character education. This study will see how future mathematics teachers' character in producing culture-based learning videos will be seen. The theme in the video that was made was ethnomathematics. The subjects in this study were prospective mathematics teachers who had implemented campus teaching programs and educational internships. With the teaching experience that is owned, it will be seen how the character of the prospective teacher during making learning videos and what character values are contained in the tape so that it can have a positive impact on students. Based on observations during the manufacturing process, most of the prospective teachers have central character values . The results of ethnomathematics-based learning videos are one of the media that can instil character values for students.